Ship Maintenance and Spare-Parts Availability for Operational Continuity of AHTS Vessels - Larsen Barasa; Marihot Simanjuntak; Brenhard Mangatur Tampubolon; Nurul Wahyuni; Siska Yoniessa (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study examines the influence of ship maintenance and spare-part availability on the operational continuity of the AHTS Transko Andalas, operated by Pertamina Marine Solutions. Using a qualitative-descriptive approach with supportive quantitative indicators, data were collected through semi-structured interviews, questionnaires, onboard observations, and document analysis. The Spare-Parts Readiness Index (SPRI) and Planned Maintenance Compliance (PMC) were applied to measure vessel preparedness. Results revealed that both maintenance and spare-part availability positively and significantly impact operational continuity, though challenges remain in procurement delays, critical maintenance compliance, and workforce competence in predictive diagnostics. Thematic analysis highlighted procurement bottlenecks, maintenance execution gaps, and human resource limitations as recurring barriers. Findings contribute to maritime operations management, shipping sustainability, and vocational education by demonstrating the interdependence of technical and human factors in sustaining offshore vessel reliability. The study emphasizes the urgency of integrated procurement reforms, condition-based maintenance, and workforce training to achieve sustainable maritime operations.